2019
DOI: 10.3389/fcimb.2019.00312
|View full text |Cite
|
Sign up to set email alerts
|

yqhG Contributes to Oxidative Stress Resistance and Virulence of Uropathogenic Escherichia coli and Identification of Other Genes Altering Expression of Type 1 Fimbriae

Abstract: Urinary tract infections (UTIs) are common bacterial infections and the vast majority of UTIs are caused by extraintestinal pathogenic Escherichia coli (ExPEC) strains referred to as uropathogenic E. coli (UPEC). Successful colonization of the human urinary tract by UPEC is mediated by secreted or surface exposed virulence factors—toxins, iron transport systems, and adhesins, such as type 1 fimbriae (pili). To identify factors involved in the expression of type 1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…We previously generated a transposon (Tn) library in UPEC reference strain CFT073 [ 28 ]. The library was subjected to osmotic and oxidative stresses as a selection for potentially decreased fitness in an environment in which the bacteria encounter host-derived stresses including osmolarity in urine and interactions with host immune cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously generated a transposon (Tn) library in UPEC reference strain CFT073 [ 28 ]. The library was subjected to osmotic and oxidative stresses as a selection for potentially decreased fitness in an environment in which the bacteria encounter host-derived stresses including osmolarity in urine and interactions with host immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that there is a link between sensitivity to oxidative stress and altered expression of type 1 fimbriae. Previous studies reported that mutations in other genes, including yeaR , rpoS , ibeA and yqhG , increased sensitivity to oxidative stress and concomitantly decreased expression of type 1 fimbriae [ 28 , 49 51 ]. Importantly, assembly of type 1 fimbriae is dependent on the oxidative state of subunit proteins in the periplasm and involves the coordinated folding of subunits through action of the oxidoreductase DsbA and the chaperone FimC, underscoring the potential effects of oxidative imbalances on fimbrial biogenesis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of proteins are able to sense α‐ketoglutarate including a 2CS named KguSR whose activity influences expression of α‐ketoglutarate dehydrogenase, succinyl CoA synthetase and type 1 fimbriae in uropathogenic E . coli (Cai et al ., 2013; Huergo and Dixon, 2015; Bessaiah et al ., 2019). Whether HK PpeS plays a similar role in P .…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli, besides its well-known roles in carbon and nitrogen metabolic pathways, α-ketoglutarate is considered as a master regulator able to activate α-ketoglutarate-sensing regulatory proteins, and that modulates cAMP (Huergo and Dixon, 2015). A variety of proteins are able to sense α-ketoglutarate including a 2CS named KguSR whose activity influences expression of α-ketoglutarate dehydrogenase, succinyl CoA synthetase and type 1 fimbriae in uropathogenic E. coli (Cai et al, 2013;Huergo and Dixon, 2015;Bessaiah et al, 2019). Whether HK PpeS plays a similar role in P. putida in spite of its low sequence similarity with KguS (10% identity) warrants further investigations.…”
Section: Inactivation Of Succinyl-coa Synthetase As a Cause Of Ttgabcmentioning
confidence: 99%